Comparative Analysis of Primary and Secondary Structure for Pea Isoamylase Isoforms Predicts Different Catalytic Properties against Glucan Substrates - Hasnain, Hussain; Cathie, Martin (WILEY‐VCH Verlag, 2009)
Abstract Screening of pea cDNA library has resulted in isolation of three different genes that encode different isoforms of isoamylase. From analysis and comparison with other isoamylase genes available from public databases and also from cDNA clones encoding isoforms of potato isoamylase, there are likely to be three isoforms of isoamylase in most (all) angiosperm genomes although so far only few plant species have their cDNA or genomic DNA characterised for these genes. Analysis of the primary structure of the ...